Biodegradation of thiocyanate by a novel strain of Burkholderia phytofirmans from soil contaminated by gold mine tailings. (22nd July 2013) - Vu, H.P.; Mu, A.; Moreau, J.W.
<x xml:space="preserve">Abstract</x> A novel B. phytofirmans strain with the capacity to degrade thiocyanate was isolated from pH approximately 6·5 soil contaminated by effluent from gold mine tailings. This Burkholderia strain uses thiocyanate as its sole nitrogen source and can grow on acetate as a sole carbon source in a minimal medium. While biodegradation of thiocyanate has been reported to occur within alkaline environments (e.g. soda lakes and wastewater from coking plants), this work presents the first observation of thiocyanate degradation by Burkholderia at pH <9·0. Our findings therefore inform remediation strategies for thiocyanate contamination in nonalkaline soils and waters impacted by gold‐mining activities. Significance and Impact of the Study This work describes thiocyanate biodegradation by a novel Burkholderia phytofirmans strain isolated from circumneutral pH gold mining‐contaminated soils. Previous reports of bacterial thiocyanate degradation have mainly focused on alkaline environments or culturing conditions (pH ≥ 9). Because cyanidation is used globally in gold mining, with thiocyanate as the major contaminant, our results will interest those working on biotechnological approaches to gold mine waste remediation.